Design and implementation of a Music Box using FPGA - Tan Kian Yiak (Universiti Malaysia Perlis, 2008)
A design and implementation of music box using FPGA is presented in this report. FPGA is a digital logic chip that can be programmed to do almost any digital function. An effort has been carried out to make the FPGA to perform like a music box. An Altera Education board which contains variety function FPGA is used. The program is written in Verilog HDL coding. Quartus II software is used to simulate the program and downloaded it into the FPGA board. Some limitations exist in the FPGA board which limits the size of the program. However, the music box functions well in general.